2017
DOI: 10.1371/journal.pone.0181152
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral 18F-FDG PET in macrophagic myofasciitis: An individual SVM-based approach

Abstract: IntroductionMacrophagic myofasciitis (MMF) is an emerging condition with highly specific myopathological alterations. A peculiar spatial pattern of a cerebral glucose hypometabolism involving occipito-temporal cortex and cerebellum have been reported in patients with MMF; however, the full pattern is not systematically present in routine interpretation of scans, and with varying degrees of severity depending on the cognitive profile of patients. Aim was to generate and evaluate a support vector machine (SVM) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Couette et al reported the unexpected death during sleep of a 37-years-old MMF patient, but the cause of death was not defined because an autopsy was rejected 22 . Blanc-Durand et al verified the statistical significance of the uniquely localised cerebral hypometabolism in the temporo-occipital cortex and cerebellum of patients with MMF compared to healthy individuals, by performing computer-aided support vector machine (SVM) classification on large and multicentric 18 F-FDG-PET cohorts 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Couette et al reported the unexpected death during sleep of a 37-years-old MMF patient, but the cause of death was not defined because an autopsy was rejected 22 . Blanc-Durand et al verified the statistical significance of the uniquely localised cerebral hypometabolism in the temporo-occipital cortex and cerebellum of patients with MMF compared to healthy individuals, by performing computer-aided support vector machine (SVM) classification on large and multicentric 18 F-FDG-PET cohorts 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Standard brain MRI was usually normal but functional neuroimaging alterations were conspicuously found, including: (1) focal brain perfusion defects assessed by SPECT (singlephoton emission computerized tomography), well correlated to both attention/memory alterations and inter-hemispheric dysconnexion [109]; (2) a characteristic pattern of posterior cerebral glucose hypometabolism assessed by FDG-PET (fluorodeoxyglucose -positron emission tomography) scanner, involving occipital cortex, hippocampus and cerebellum, and predictive of MMF detection at muscle biopsy [110][111][112][113][114].…”
Section: Clinical Characterizationmentioning
confidence: 99%
“…(6) highly consistent functional neuroimaging changes (SPECT and FDG-PET scanner) in MMF patients, not attributable to chronic pain or depression, indicating that MMF is detected in an homogeneous subset of patients with stereotyped condition [109][110][111][112][113][114]; (7) perfect similarity of the MMF syndrome with the GWI multisymptom complex [116] defined by CDC [55] which has been uniquely associated with vaccine exposure in military personnel non-deployed in the Persian gulf [53].…”
Section: Consistency Analysismentioning
confidence: 99%